Maulānā ʻAbdulmājid Daryābādī : ḥayāt va ḵẖidmāt - ʻAbdulqavī; Abdul Majid, 1892-1977 (Maulānā ʻAbdulmājid Ikāḍamī, 1978)
Collection of writings on the Indian Islamic scholar Abdul Majid, 1892-1977; commemoration volume.